1901 N J. Laws 265 - (:unkn) unknown (My University, 1901)
Ch. 120, 14: It shall be unlawful to hunt with a hound or hounds, or with fire-arms or weapons of any kind, or to carry a gun in the woods or fields or on the waters on the Sabbath day, commonly called Sunday, under a penalty of twenty dollars for each offence.
Keywords: HUNTING REGULATION